Parapharyngeal space lipoma causing sleep apnoea - Abdullah, B.J.; Liam, C.K.; Kaur, H.; Mathew, K.M. (British Institute of Radiology, 1997)
Lipoma of the parapharyngeal space is very rare, only three cases having been reported in the literature. A parapharyngeal space lipoma causing obstructive sleep apnoea has not been reported before. A 60-year-old man presented at the ear, nose and throat (ENT) clinic with a history of loud snoring associated with sleep apnoea secondary to a right parapharyngeal space lipoma. The causes of sleep apnoea and the radiological features of a parapharyngeal space lipoma are discussed.